2018
DOI: 10.1158/1078-0432.ccr-18-0982
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for Tumor-Selective Disruption of Androgen Receptor Function in the Spectrum of Prostate Cancer

Abstract: Testosterone suppression in prostate cancer is limited by serious side effects and resistance via restoration of androgen receptor (AR) functionality. ELK1 is required for AR-dependent growth in various hormone-dependent and castration-resistant prostate cancer models. The amino-terminal domain of AR docks at two sites on ELK1 to coactivate essential growth genes. This study explores the ability of small molecules to disrupt the ELK1-AR interaction in the spectrum of prostate cancer, inhibiting AR activity in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…Nonetheless, our findings uncover an important functional relationship between USP17 and ELK-1 in its conserved role as ERK responder and activator of mitogenic gene expression (Figure 7F). Indeed, the impact of USP17 on ELK-1 function may extend beyond its relationship with ERK, given the recent discovery of a physical and functional cooperation between ELK-1 and androgen receptor in advanced prostate cancer (69,70). A next priority will be to identify the ubiquitin E3 ligase(s) specifically responsible for mono-ubiquitination of ELK-1.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, our findings uncover an important functional relationship between USP17 and ELK-1 in its conserved role as ERK responder and activator of mitogenic gene expression (Figure 7F). Indeed, the impact of USP17 on ELK-1 function may extend beyond its relationship with ERK, given the recent discovery of a physical and functional cooperation between ELK-1 and androgen receptor in advanced prostate cancer (69,70). A next priority will be to identify the ubiquitin E3 ligase(s) specifically responsible for mono-ubiquitination of ELK-1.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, expression of a hypo-ubiquitinated ELK-1 mutant, but not wild-type ELK-1, partially rescued the proliferation defect caused by USP17 depletion in HEK293T cells, illustrating the contribution of this mechanism towards mitogen signalling [ 86 ]. The established role for ELK-1 as an AR tethering element suggests that further studies are warranted to decipher whether USP17 acts on ELK-1 to promote tumorigenesis in PCa [ 91 , 92 , 93 ].…”
Section: Tcfs Showcase Mono-ubiquitination As a Non-destructive Mode Of Repressionmentioning
confidence: 99%
“…15 Research by Siddiqui et al showed that the green tea compound epigallocatechin-3-gallate could inhibit AR in silico and inhibit cell lines from prostate cancer. 16,17 In this study, only one extracted compound from green tea was tested and it did not use ADT control for comparison with AR.…”
Section: Introductionmentioning
confidence: 99%